A new species of succulent plant discovered in limestone areas of Kyushu, Japan: Sedum kawaraense (Crassulaceae) - Ito, Takuro; Kanemitsu, Hironobu; Hoson, Taishi; Yahara, Tetsukazu (Phytotaxa, 2023)
An unknown species of the genus Sedum was discovered in Kawara-dake and Ryu-ga-hana, limestone mountains in Kyushu, Japan. The present study aimed to clarify the taxonomic status of the unknown Sedum species through morphological and ecological comparisons and molecular phylogenetic analysis using ITS sequences based on comprehensive taxon sampling of sect. Sedum in East Asia. Morphologically and ecologically, the unknown species was most similar to S. lipingense in China, but was distinguished by having larger spatulate rosulate leaves and more flowers per flowering stem. Phylogenetically, it belonged to a clade with four Chinese endemics including S. lipingense and two other species widely distributed in East Asia. The clade showed polytomy at the base, but the unknown species was genetically differentiated from the other species. Therefore, we describe the unknown species from Kawara-dake as a new species, S. kawaraense.